A Systematic Review and Meta‐Analysis of Taste Dysfunction in Chronic Rhinosinusitis. (1st July 2020) - Xie, Deborah X.; Leland, Evelyn M.; Seal, Stella M.; Lin, Sandra Y.; Rowan, Nicholas R.
Abstract : Objectives: Patients with chronic rhinosinusitis (CRS) often describe alterations in sense of taste. These complaints have historically been attributed to olfactory dysfunction; however, there is evidence of direct, objective, gustatory disturbances in the setting of CRS that are not thoroughly characterized. This study sought to investigate and summarize gustatory dysfunction experienced by patients with CRS. Methods: PubMed, EMBASE, Cochrane Library, Web of Science, and Scopus databases were reviewed following PRISMA guidelines. English language, original studies investigating objective taste in adult patients with CRS were included. A meta‐analysis with inverse variance, random‐effects model was performed. Results: Of 2750 studies screened, 11 articles with 471 unique patients were included. Patients with CRS exhibit worse gustatory function compared to healthy controls (standardized mean difference 0.94 [95% CI, 0.44–1.45]). Hypogeusia was identified in 32/95 (33.7%) patients from three studies that used methods with a validated definition of hypogeusia. Older age, male gender, and smoking history were associated with taste dysfunction, while objective gustatory and olfactory dysfunction were not correlated. Subjective taste and quality of life measures were also not associated with objective taste. The impact of sinus surgery on objective taste is unclear. Conclusion: Approximately 34% of patients with CRS experience hypogeusia. Neither olfactory function nor subjective taste were associated with objective gustatory function. Given the substantial prevalence of taste dysfunction patients with CRS, there is significant potential for growth in understanding of pathogenesis, impact on quality of life, and potential treatment strategies of taste impairment in the CRS patient population. Level of Evidence: 1 Laryngoscope, 131:482–489, 2021